Regulation of mitochondrial oxidative stress by β-arrestins in cultured human cardiac fibroblasts - Jennifer L. Philip; Md. Abdur Razzaque; Mei Han; Jinju Li; Tiju Theccanat; Xianyao Xu; Shahab A. Akhter (The Company of Biologists, 2015)
Oxidative stress in cardiac fibroblasts (CFs) promotes transformation to myofibroblasts and collagen synthesis leading to myocardial fibrosis, a precursor to heart failure (HF). NADPH oxidase 4 (Nox4) is a major source of cardiac reactive oxygen species (ROS); however, mechanisms of Nox4 regulation are unclear. β-arrestins are scaffold proteins that signal in G-protein-dependent and -independent pathways; for example, in ERK activation. We hypothesize that β-arrestins regulate oxidative stress in a Nox4-dependent manner and increase fibrosis in HF. CFs were isolated from normal and failing adult human left ventricles. Mitochondrial ROS/superoxide production was quantitated using MitoSox. β-arrestin and Nox4 expressions were manipulated using adenoviral overexpression or short interfering RNA (siRNA)-mediated knockdown. Mitochondrial oxidative stress and Nox4 expression in CFs were significantly increased in HF. Nox4 knockdown resulted in inhibition of mitochondrial superoxide production and decreased basal and TGF-β-stimulated collagen and α-SMA expression. CF β-arrestin expression was upregulated fourfold in HF. β-arrestin knockdown in failing CFs decreased ROS and Nox4 expression by 50%. β-arrestin overexpression in normal CFs increased mitochondrial superoxide production twofold. These effects were prevented by inhibition of either Nox or ERK. Upregulation of Nox4 seemed to be a primary mechanism for increased ROS production in failing CFs, which stimulates collagen deposition. β-arrestin expression was upregulated in HF and plays an important and newly identified role in regulating mitochondrial superoxide production via Nox4. The mechanism for this effect seems to be ERK-mediated. Targeted inhibition of β-arrestins in CFs might decrease oxidative stress as well as pathological cardiac fibrosis.